2018
DOI: 10.1111/apa.14433
|View full text |Cite
|
Sign up to set email alerts
|

Extrauterine growth restriction was associated with short stature and thinness in very low birthweight infants at around six years of age

Abstract: Extrauterine growth restriction was significantly associated with short stature and thinness in VLBW infants at around six years, irrespective of the degree of SGA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…However, to draw comparisons between different centers is di cult not only because de nition of EUGR and reference growth charts differ, but also because maternal and clinical characteristics of the study population, time at EUGR evaluation (36 weeks, 40 weeks PMA, discharge) and choice of ΔSDS threshold when applying the longitudinal-EUGR de nition (> 1, >2 SDS), changes. EUGR rates from NICUs of high-income countries similar to ours, evaluated at discharge, varied from 17% to 77.2% for the cross-sectional EUGR [4,[25][26][27][28][29], from 29.8-39.1% for longitudinal-1 de nition [30,31] and from 5.2-13% for longitudinal-2 EUGR [30][31][32].…”
Section: Discussionmentioning
confidence: 63%
“…However, to draw comparisons between different centers is di cult not only because de nition of EUGR and reference growth charts differ, but also because maternal and clinical characteristics of the study population, time at EUGR evaluation (36 weeks, 40 weeks PMA, discharge) and choice of ΔSDS threshold when applying the longitudinal-EUGR de nition (> 1, >2 SDS), changes. EUGR rates from NICUs of high-income countries similar to ours, evaluated at discharge, varied from 17% to 77.2% for the cross-sectional EUGR [4,[25][26][27][28][29], from 29.8-39.1% for longitudinal-1 de nition [30,31] and from 5.2-13% for longitudinal-2 EUGR [30][31][32].…”
Section: Discussionmentioning
confidence: 63%
“…Furthermore, preterm infants usually suffer from nutrients (e.g., vitamin A, D, iron) insufficiency [2, 3]. Ultimately birth weight, a decrease in z-score for body weight or length is considered a predictor of growth retardation; at the same time, very low birth weight might be a risk factor for the subsequent occurrence of growth hormone deficiency [15,30]. Therefore, we should thoroughly consider all issues mentioned above when conducting nutritional risk screening for preterm infants.…”
Section: Nrsp Subscale 1 Was Preterm-infant-specificmentioning
confidence: 99%
“…Nutrients required for catch-up growth are sufficient energy, protein, vitamins, and minerals [13, 14]. Studies also found that extrauterine growth retardation and decrease in z -score of body weight or length were significant predictors of growth failure in early childhood [15]. Consequently, when developing a nutritional risk screening tool specific for preterm infants, the issues mentioned above should be under consideration.…”
Section: Introductionmentioning
confidence: 99%
“…Extrauterine growth restriction (EUGR), defined as an anthropometric measure that is lower than the 10th percentile, is prevalent and occurs in the majority of very preterm infants [ 1 ]. Preterm infants with EUGR at discharge have been shown to develop short stature, poor neurodevelopmental outcomes, and cardiovascular and metabolic problems after they grow up [ 2 , 3 , 4 , 5 , 6 ]. EUGR has been linked to intrauterine growth restriction, maternal preeclampsia, low gestational age (GA), feeding intolerance, delay in first enteral feeding, and inadequate nutritional supplement [ 1 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%